Negative thermal expansion properties of Cu1.8Co0.2V2O7. (1st September 2022) - Chen, Lu; Shao, Qi; Hu, Yameng; Chao, Mingju; Guo, Juan; Gao, Qilong; Liang, Erjun
Abstract: Cu1.8 Co0.2 V2 O7 with negative thermal expansion ( α l = −13.2 × 10 −6 K −1, 153–773 K) was prepared by adopting the solid phase method. The crystal structure, microstructure, thermal expansion properties, and Raman spectra of Cu1.8 Co0.2 V2 O7 were analyzed by using variable temperature X-Ray diffraction (XRD), dilatometer, and variable temperature Raman spectroscopy, respectively. In the crystal structure of Cu1.8 Co0.2 V2 O7, one V 5+ and four O 2− form [VO4 ] tetrahedra, two [VO4 ] tetrahedra form [V2 O7 ] structures by sharing top-angle oxygen atoms, one Cu 2+ (Co 2+ ) and five O 2− are connected to form a [CuO5 ] tetragonal units, [CuO5 ] and [VO4 ] are connected by sharing O2 and O3 atoms to form a chain to produce a layered staggered structure.The results of variable temperature XRD indicated that with the gradual increase of temperature, the transverse vibration of O atoms shared by [CuO5 ] and [VO4 ] increases and the coupling effect between [CuO5 ] and [VO4 ] polyhedra is enhanced. Therefore, the angle between Cu–O2 –V and Cu–O3 –V and the unit cell parameters a and c gradually decrease, leading to a gradual decrease in the Cu1.8 Co0.2 V2 O7 inner layer spacing. This work provides a new negative thermal expansion material. Highlights: Cu1.8 Co0.2 V2 O7 is monoclinic phase structure. No structural phase transition occurs when the temperature increases. Cu1.8 Co0.2 V2 O7 was prepared by solid phase method. Its expansion coefficient is −13.2 × 10 −6 K −1 (153-773 K). The decrease of the angle between Cu–O2 –V and Cu–O3 –V is the main reason for the reduction of cell volume.